On-Line Analytical Instrumentation in the Water Industry — Problems and Practical Solutions - R. Briggs DTech, CEng, FIEE, FIPHE, FInstMC, MInstWPC (Measurement + Control, 1983)
Part 1 of this article was published in the March issue and dealt with problems. It covered the background, needs and priorities in the water industry, also overall system considerations and developments in measurement technology.